Advances in Piston Rings Modelling and Design - Senatore, Adolfo; Aleksendric, Dragan (Recent Patents on Engineering, 2013)
The lubrication of the piston ring has been an important research matter for many years because it is generally accepted that the interaction at the ring-cylinder wall interface provides considerable effects on friction, wear, oil consumption and power loss in internal combustion engines. This paper after a historical overview presents in the first section the main physical phenomena considered by the literature for the design and the numerical simulation of frictional behaviour of piston rings. In the second section the first patents appeared since 1920s are briefly discussed before the more recent ones which deal with novel materials, innovative manufacturing methods, optimised shape and novel nano-lubricants.
Keywords: engine friction